Archean rare-metal pegmatites in Zimbabwe and Western Australia : geology and metallogeny of pollucite mineralisations /: geology and metallogeny of pollucite mineralisations. ([2019]) - Dittrich, Thomas; Seifert, Thomas; Schulz, Bernhard; Hagemann, Steffen; Gerdes, Axel; Pfänder, Jörg
No abstract available